Spontaneous rupture of hemorrhagic hepatic cyst: two case reports - Ichiya Chogahara; Akihiko Oshita; Hideki Nakahara; Toshiyuki Itamoto (Surgical Case Reports, 2022)
Abstract Background Spontaneous rupture of a hemorrhagic hepatic cyst is extremely rare. There is no standard treatment recommended for this condition. We report two cases of hemorrhagic hepatic cysts that spontaneously ruptured and were successfully treated with laparoscopic deroofing. We review the literature and discuss the characteristic features of spontaneous rupture of hemorrhagic hepatic cysts and their treatment. Case presentation The first patient was an 85-year-old man admitted for sudden-onset right hypochondralgia and fever. Computed tomography revealed a 13-cm hepatic cyst occupying the right lobe of the liver and spontaneous rupture of the cyst. Laparoscopic deroofing was performed and continuous oozing from the cystic wall was found. Histological examination revealed a simple hepatic cyst. The patient was discharged on postoperative day 6. In the second case, a 77-year-old woman who had been followed up for a simple hepatic cyst (13 cm) was admitted for sudden onset of right hypochondralgia. Computed tomography demonstrated a 9.9-cm hepatic cyst occupying segment 4 of the liver. Laparoscopic deroofing was performed and continuous oozing from the cystic wall was observed. Histological examination revealed a simple hepatic cyst. The patient was discharged on postoperative day 6. Conclusion Laparoscopic deroofing was performed in patients with spontaneous rupture of hemorrhagic nonparasitic hepatic cysts.